In smokers, Sonic hedgehog modulates pulmonary endothelial function through vascular endothelial growth factor - Priscilla Henno; Stanislas Grassin-Delyle; Emeline Belle; Marion Brollo; Emmanuel Naline; Edouard Sage; Philippe Devillier; Dominique Israël-Biet (Respiratory Research, 2017)
Abstract Background Tobacco-induced pulmonary vascular disease is partly driven by endothelial dysfunction. The Sonic hedgehog (SHH) pathway is involved in vascular physiology. We sought to establish whether the SHH pathway has a role in pulmonary endothelial dysfunction in smokers. Methods The ex vivo endothelium-dependent relaxation of pulmonary artery rings in response to acetylcholine (Ach) was compared in 34 current or ex-smokers and 8 never-smokers. The results were expressed as a percentage of the contraction with phenylephrine. We tested the effects of SHH inhibitors (GANT61 and cyclopamine), an SHH activator (SAG) and recombinant VEGF on the Ach-induced relaxation. The level of VEGF protein in the pulmonary artery ring was measured in an ELISA. SHH pathway gene expression was quantified in reverse transcriptase–quantitative polymerase chain reactions. Results Ach-induced relaxation was much less intense in smokers than in never-smokers (respectively 24 ± 6% and 50 ± 7% with 10−4M Ach; p = 0.028). All SHH pathway genes were expressed in pulmonary artery rings from smokers. SHH inhibition by GANT61 reduced Ach-induced relaxation and VEGF gene expression in the pulmonary artery ring. Recombinant VEGF restored the ring’s endothelial function. VEGF gene and protein expression levels in the pulmonary artery rings were positively correlated with the degree of Ach-induced relaxation and negatively correlated with the number of pack-years. Conclusion SHH pathway genes and proteins are expressed in pulmonary artery rings from smokers, where they modulate endothelial function through VEGF.